Soil microbiota plays a key regulatory role in the outbreak of tobacco root rot - Li, Pengfei; Gu, Songsong; Zhu, Yanmei; Xu, Tianyang; Yang, Yishuai; Wang, Zhengqiang; Deng, Xiangdong; Wang, Bin; Li, Wei; Mei, Wenqiang; Hu, Qiulong (Frontiers in Microbiology, 2023)
Introduction Root rot caused by the fungal pathogen Fusarium sp. poses significant challenges to tobacco cultivation in China, leading to major economic setbacks. The interplay between this pathogen and the wider soil microbial community remains poorly understood. Methods High-throughput sequencing technology was utilized to evaluate soil prokaryotic, fungal, and protistan communities. We compared microbial communities in infected soils to those in healthy soils from the same field. Additionally, the influence of pH on the microbial communities was assessed. Results Infected soils displayed elevated levels of soil nutrients but diminished observed richness across prokaryotic, fungal, and protistan groups. The pathogenic fungi Fusarium solani f sp. eumartii’s abundance was notably increased in infected soils. Infection with F. solani significantly altered the soil’s microbial community structure and interactions, manifested as a decrease in network scale and the number of keystone species. An evaluation of prokaryotes’ role in F. solani’s invasion revealed an increased number of connecting nodes in infected soils. Additionally, relationships between predatory protists and fungi were augmented, whereas predation on F. solani declined. Discussion The study underscores the significance of comprehending the interactions among soil microorganisms and brings to light the susceptibility of soil microbial communities to pathogen invasion. It offers insights into the multifaceted relationships and potential vulnerabilities within the soil ecosystem in the context of Fusarium sp. invasion.